Water vapor therapy and polymyalgia rheumatica: Coincidental? - Joshua Lee; Sandy Lee; Tracy U. Nguyen-Oghalai (Journal of Family Medicine and Primary Care)
Polymyalgia rheumatica (PMR) is an inflammatory rheumatic condition characterized by pain and stiffness around the shoulders and hip girdles, an elevated erythrocyte sedimentation rate (ESR) or C-reactive protein (CRP) and a dramatic response to corticosteroids. It is usually seen in adults aged over 50 years; about 30% also have giant cell arteritis. Its etiology is unknown. A 72-year-old male received water vapor therapy, a novel, minimally invasive therapy for benign prostate hypertrophy (BPH). On postoperative day 1, he developed severe shoulder pain and weakness, with difficulty with lifting his arms above his head, and hip pain and weakness, with difficulty getting out of a bed or chair. Laboratory results showed elevated ESR and CRP, but a normal creatine kinase level. The patient received low-dose prednisone and had prompt symptom relief. This case illustrates that a diagnosis of PMR after water vapor therapy can be easily overlooked.